The family structure and cultural practices of Garo community in Bangladesh: An overview - Jalil, Md Abdul; Oakkas, Mohammad Ali (Himalayan Journal of Sociology and Anthropology, 2012)
The Garo is one of the marginalised ethnic minority groups in Bangladesh originally migrated from Tibet. They have been living in the different areas of Bangladesh for few centuries with mainstream Bengali community. However, they hold distinct cultural tradition and social system not consistent with mainstream Bengali people although they frequently interact with each other. Based on ethnographic study, the present paper argues that although Garo’s traditional family pattern and cultural practices are changing gradually largely because of frequent interaction with mainstream Bengali people and influence of Christianity, traditional norms and practices still dominate their family and cultural life to a considerable extent. DOI: http://dx.doi.org/10.3126/hjsa.v5i0.7042 Himalayan Journal of Sociology & Anthropology-Vol. V (2012) 95-110